Internet of Things-Based Steam Pump Motor Protection Due to Voltage Unbalance - Bagas Aji Saputra; Edy Prasetyo Hidayat; Afif Zuhri Arfianto (Universitas Muhammadiyah Yogyakarta, 2020)
PLTGU is a gas and steam power plant, producing electrical energy of 3x526 MW. The PLTGU generation process has several supporting components, one of which is a three-phase induction motor. It requires a balanced three-phase supply voltage in its operation. The problem that frequently occurs is unbalanced voltage supply, causing an imbalance of current going to the motor stator, if not directly corrected. It causes a high temperature on the motor, possible to cause a fire. Based on the problems, a system for monitoring the protection of steam pump motorcycles due to voltage unbalance based on the Internet of Things is designed. It used a 1-phase AC Adapter voltage sensor, a current sensor SCT-013, an Arduino Uno as the processor, and a web to display the system. The test results showed that the sensor could work well. It could read voltage with an error percentage not exceeding 1%. The percentage error of the current sensor SCT-013 was 5.15%, but the value difference between the sensor and the Avo meter was 0.01. The system was displayed on the web to make to monitor the motor condition more easily